Familial and Clinical Correlates in Depressed Adolescents with Borderline Personality Disorder Traits - Guilé, Jean-Marc; Huynh, Christophe; Breton, Jean-Jacques; De La Rivière, Sébastien Garny; Berthiaume, Claude; St-Georges, Marie; Labelle, Réal (Frontiers in Pediatrics, 2016)
Introduction: Chart review is a low-cost, but highly informative, method to describe symptoms, treatment and risk factors associated with Borderline Personality Disorder (BPD) and to adapt screening and intervention to clinical reality. Previous chart review studies report more aggressiveness/anger and psychotic features in youths with BPD. They show that adverse family environment and parental psychopathology constitute important factors for BPD pathology. Objectives: To examine clinical characteristics of depressed BPD adolescents (12-17 years old) outpatients according to gender and to explore variables which are associated with BPD traits. Methods: A retrospective chart review using the Child and Adolescent Version of the Retrospective Diagnostic Instrument for Borderlines was conducted on 30 depressed BPD adolescents with BPD traits and 28 non-BPD depressed patients without BPD traits. Participants who reached the C-DIB threshold for BPD were included in the BPD traits group. The Child and Adolescent Version of the Retrospective Diagnostic Interview for Borderlines was used to determine the presence of BPD. Comparisons analyses were performed using Pearson’s Chi-square test. Associated factors were determined using regression analyses. Results: BPD traits participants outpatients were characterised by higher family problems (parental psychopathology, parent disagreement/argument, parent-child relational problem), more aggressive symptoms, and higher rates of family intervention and hospitalisation. A number of familial factors (parental history of delinquency, substance use, or personality disorders, having siblings, parental disagreement/argument in boys) were associated with BPD symptomatologytraits. Attention seeking and problematic functioning (does not adapt well to group activities) were also associated with BPD traits. Discussion: Our study stresses the need to assess BPD traits in adolescent psychiatric evaluation, especially in presence of aggressive behaviours, family problems and attention seeking. Our results also highlight the importance of exploring family characteristics intervention in adolescents with BPD traits.